Adult‐onset atypical teratoid/rhabdoid tumor featuring long spindle cells with nuclear palisading and perivascular pseudorosettes. Issue 1 (14th June 2016) - Horiguchi, Hidehisa; Nakata, Satoshi; Nobusawa, Sumihito; Uyama, Shinichi; Miyamoto, Tadashi; Ueta, Hiromi; Fujimoto, Naomi; Yokoo, Hideaki
Abstract : Atypical teratoid/rhabdoid tumors (AT/RTs) are rare malignant neoplasms of the CNS that preferentially affect young children. We herein report an adult case of AT/RT surviving for more than 5 years with the residual tumor. The patient, a 24‐year‐old man at onset, presented with a contrast‐enhancing mass lesion in the left occipital lobe, and underwent partial tumor resection. Histologically, the tumor was predominantly composed of long spindle cells exhibiting nuclear palisading and perivascular pseudorosettes, which appeared to mimic mesenchymal, ependymal and Schwann cell tumors. A small number of isolated rhabdoid cells did not initially attract attention, and a tentative pathological diagnosis of a malignant mesenchymal tumor was made. In a later examination focusing on the small areas of rhabdoid cells, the extensive loss of the nuclear expression of INI1 was detected in all areas. Diffuse staining with vimentin and focal immunoreactivity for epithelial membrane antigen and alpha smooth muscle actin were observed not only in AT/RT foci, but also in spindle cell areas. Thus, polyphenotypic immunoreactivity was evident. Fluorescence in situ hybridization revealed a homozygous deletion of chromosome 22q covering the INI1 locus. Histopathological differences between infant and adult AT/RTs currently remain unclear. In the case of a malignant adult brain tumor showing a hardly classifiable morphology and immunophenotypic diversity, an analysis of the INI1 status may contribute to an accurate diagnosis.